Sustentabilidade de concretos com misturas binárias de pozolanas e resíduos de demolição de concreto com ênfase na avaliação e custo do ciclo de vida - Lima, Cristian Jonathan Franco de (2018)
With the increasing consumption of natural resources worldwide, great concern about the environment is generated, making sustainability a focus on the quality of life and survival of living beings. In order to reduce these impacts, most segments of society have sought to rethink their production strategies, especially the construction industry, which is one of the largest consumers of natural resources, waste generators and harmful greenhouse gas emissions. In this context, the present study aims to study different concrete traces used for the design of a pillar, using two types of cement (CP IV and CP V-ARI), two types of pozolanas (rice husk ash and fly ash ), as well as a large aggregate of concrete demolition waste, in order to verify the main environmental impacts caused by each mix and to define the best concrete / pillar alternative from an environmental / sustainable and economic point of view. Previously, the traits to be used were defined, using the Abrams curve and dosage studies, and in a total of ten distinct traits, five were dosed at fck = 25MPa, and five dosed at fck = 35MPa; Afterwards, the moldings of the specimens were carried out according to the established traces, followed by the tests of Resistance to Axial Compression, Elasticity Modulus, Penetration of Chloride Ions by Immersion, Life Cycle Cost (CCV) and Cycle Analysis of Life (LCA). With respect to the Axial Compression Resistance, it was observed that the substitution of the natural aggregate (AGN) for recycled concrete aggregate (ARC) was detrimental, causing a significant decrease in resistance, which was counterbalanced by the use of pozzolans, as well as, alteration of the a / g ratios, and in the Modulus of Elasticity test a similar trend was observed. Regarding the durability, it was verified that the lower penetration coefficients of chloride ions, in general, occurred for the traces in which CP V cement was used, besides the partial replacement of the AGN by ARC in percentage of 15% and partial replacement of cement by pozolana in percentage of 25%. As for CCV and LCA, the cradle-to-grave approach was applied, thus, the pillars using concrete dosed to fck = 35MPa caused smaller impacts throughout its useful life. When the sustainability-financial integration was carried out, the pillar dosed at fck = 35MPa, using CP V cement, 15% of AGN replacement by ARC and substitution of 25% of cement per rice hull ash was obtained as the best alternative.